Sagot :
Answer:
[tex]\mathrm{1.\:8\left(y-2\right)\left(y^2+2y+4\right)}[/tex]
[tex]\mathrm{2.\:(5x+2y)(25x^2-10xy+4y^2)}[/tex]
[tex]\mathrm{3.\:(3x-5y)(9x^2+15xy+25y^2)}[/tex]
[tex]\mathrm{4.\:(ab^2-x)(a^2b^4+ab^2x+x^2)}[/tex]
Step-by-step explanation:
[tex]\mathrm{1.\: 8y^3-64}\\\mathrm{=8\left(y^3-8\right)}\\\mathrm{=8\left(y-2\right)\left(y^2+2y+2^2\right)}\\\mathrm{=8\left(y-2\right)\left(y^2+2y+4\right)}[/tex]
[tex]\mathrm{2.\: 125x^3 + 8y^3}\\\mathrm{=\left(5x\right)^3+\left(2y\right)^3}\\\mathrm{=\left(5x+2y\right)\left(25x^2-10xy+4y^2\right)}[/tex]
[tex]\mathrm{3.\: 27x^3-125y^3}\\\mathrm{=\left(3x\right)^3-\left(5y\right)^3}\\\mathrm{=\left(3x-5y\right)\left(9x^2+15xy+25y^2\right)}[/tex]
[tex]\mathrm{4.\: a^3b^6-x^3}\\\\\mathrm{=\left(ab^2\right)^3-x^3}\\\mathrm{=\left(ab^2-x\right)\left(a^2b^4+ab^2x+x^2\right)}[/tex]